WolframAlpha como herramienta educativa para apoyar el aprendizaje de Álgebra Lineal - Chalán Gualán, Elsa Ximena (2024)
The use of technological tools in education, such as WolframAlpha, has revolutionized the learning of linear algebra by offering interactive and analytical resources that facilitate the understanding and application of complex mathematical concepts. The objective of the present work was to analyze the relationship between the application of WolframAlpha and the learning of linear algebra. A qualitative approach of documentary type was used, adopting a non-experimental design of a transversal nature. The research methodological tools used were the content fiche and content cards techniques. The study showed that WolframAlpha improves linear algebra learning by providing interactive tools that allow students to ask questions in everyday language and receive accurate answers quickly. Additionally, the platform offers graphics and visualizations that are essential for understanding abstract concepts. WolframAlpha has been identified as having beneficial features for teaching linear algebra, standing out for its detailed explanations and graphical visualizations that facilitate the understanding of complex algebraic procedures. Keywords: WolframAlpha, linear algebra, mathematics, interactive learning, technological tools